Petrological features of forming the rare-earth Anadolsk deposit (Ukraine) - Sheremet, Ye.M.; Kryvdyk, S.G. (Reports of the National Academy of Sciences of Ukraine, 2017)
New data on petrological geochemical features of the formation of the Anadolsk rare-earth deposit allowing one to conclude about its genesis are presented. According to the authors, the origin of Anadolsk rare-earth (orthite) deposit in view of the characteristics of a composition of rare-earth elements, orthite, britolit, and a substantially carbon dioxide fluid is likely due to the deep mantle alkaline fluids, whose penetration resulted in the formation of the Azov and Mazurovsky deposits and all the rare-metal-rare earth occurrences within the Eastern Priazovie, as well as extensive development of fenitized rocks in the region. The Anadolsk orthites mineral of occurrence is the first opened occurrence among the series of discovered zones of alkaline metasomatites of the East Pryazovie of the Ukrainian Shield.